Filogenia molecular do gênero Actinocephalus (Koern.) Sano (Eriocaulaceae) e suas implicações taxonômicas - Michelle Pires Tannure (2013)
The Eriocaulaceae family is easily distinguished from other monocots by presence of the inflorescence with umbellate arrangement of capitula. It is divided into 10 genera with pantropical distribution and has as main diversity centre the Espinhaço Range in the states of Minas Gerais and Bahia. Phylogenetic analyses realized in Eriocaulaceae supported new taxonomic interpretations onto family, but much still remains to be done to establish the relationship inter and infra-generic, being necessary more studies in some taxons specifics. In this context, the Actinocephalus genus, recently elevated to genus status, was inserted into clade composed for Paepalanthus species pertaining to different sections. Paepalanthus subsect. Aphorocaulon exhibited a large morphologic similarity with Actinocephalus were sinonimized in the genus. The objective of this work was to test the monophyly of the genus Actinocephalus, based in the higher sampling, and to elucidat phylogenetic relationships within the lineages of Paepalanthus. The analysis was based on molecular data (regions trnL-trnF, psbA-trnH and ITS), associated with the morphological and biogeographic data. We sampled leaves of 38 species of Actinocephalus (being 49 identified species in the genus) and 48 of Paepalanthus, in addition to three species of the genus Comanthera used as outgroup. The monophyly of Actinocephalus was strongly supported by molecular and morphologhic data (with the inclusion of P. camptophyllus and P. macrocephalus). However, the relanthioships intragenerics of Actinocephalus not could be established based in molecular data. Among the established relationship based on morphological data, species that had an elongate axis, umbellate arrangement of capitula, paraclades fasciculated or unique in the capitula were synapomorphies for the definition of groups more close phylogenetically. Actinocephalus is a group morphologically well circumscribed, which was evidenced on molecular data, differently of Paepalanthus that was polifiletico in nearly all its infrageneric categories. This large variability present in Paepalanthus permitted the grouping of species not related phylogenetically, as was the case of P. sect. Aphorocaulon, P. camptophyllus and P. macrocephalus. Actinocephalus is endemic in Brazil and has as its main center of diversity the Planalto Diamantina.